2018
DOI: 10.3390/en11123536
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study for the Assessment of the Measurement Uncertainty Associated with Electric Powertrain Efficiency Using the Back-to-Back Direct Method

Abstract: Brushless electric motors are used intensively in the industrial automation sector due to the motors low inertia and fast response. According to the International Electrotechnical Commission, IEC 60034-2-1, the efficiency of a three-phase electric machine (excluding machines for traction vehicles) can be determined by direct or indirect techniques. In the case of small traction motors (<10 kW), direct methods are used extensively by manufacturers, even if no standard has been published or scheduled by the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Several researchers have been studying the details of electric vehicle technology so that their overall efficiency and performance can be improved. Hannan et al reviewed the various aspects of hybrid electric vehicles [8], Du and Ouyang studied policy impact on the growth of the Chinese EV market [9], while De Santis et al simulated the effect of using a back-to-back dual-motor mounting on powertrain efficiency [10]. In a more recent paper by Li et al, the powertrain efficiency of different configurations and resource types was compared [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have been studying the details of electric vehicle technology so that their overall efficiency and performance can be improved. Hannan et al reviewed the various aspects of hybrid electric vehicles [8], Du and Ouyang studied policy impact on the growth of the Chinese EV market [9], while De Santis et al simulated the effect of using a back-to-back dual-motor mounting on powertrain efficiency [10]. In a more recent paper by Li et al, the powertrain efficiency of different configurations and resource types was compared [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, electric vehicles (EVs) have become more and more popular all over the world, and EVs will reduce environmental pollution and CO 2 emission and achieve a high energy efficiency [1,2]. Moreover, the development and improvement of key technologies with respect to batteries and charging infrastructure as well as electric motors and control increase the attractiveness of EVs [3][4][5]. At the same time, the use of EVs as a sustainable and efficient alternative to traditional diesel-and petrol-based vehicles makes the decarbonization of transport possible in the literature [2].…”
Section: Introductionmentioning
confidence: 99%
“…A review on EV technology development in key fields, such in the battery, charging, the electronic motor, charging infrastructure, and emerging technology, was shown in a literature study [4]. In order to evaluate the efficiency and associated accuracy of the power train of a light electric vehicle, in [5] the authors verified the feasibility of the back-to-back direct method. Some vehicle to grid (V2G) services, such as reactive regulation, motor starting, and transient conditions of renewable sources, were applied in EVs, which confirmed that this service does not engage the battery or require small amounts of battery charge in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Power input to the servomotor [40] is determined as a product of the measured voltages (U) and the electric current (I) [41] across the servomotor using the following equation ( 8):…”
Section: Efficiency Of the Propulsion Systemmentioning
confidence: 99%